Enhanced detection of overt HBV infection in chronic HCV carriers. (March 2023) - Mizzoni, K.; Meschi, S.; Garbuglia, A.R.; Galli, C.; Maggi, F.
Abstract : Introduction: Hepatitis B (HBV) and hepatitis C (HCV) virus coinfection are frequent in subjects at high-risk, with most HBV infections in chronic HCV carriers being apparently inactive (HBsAg negative and anti-HBc positive). HCV treatment may lead to HBV reactivation, more frequently in cases with a low-level HBV replication undetectable by current HBV serological assays. Aim: To unveil active HBV infections in a cohort of HCV-infected individuals by employing an HBsAg assay with higher sensitivity. Methods: We selected a single sample from each of 100 HCV-RNA positive, untreated patients admitted over the last three years. Sera were analyzed by Abbott ARCHITECT assays for HBsAg, by both the current (HBsAg Qual II) and a new (HBsAg Next) version, and for anti-HBc, anti-HBs and HIV. Results: Sixty-six were males and the median age was not significantly different between genders, with 87% of all subjects aged >43 years. The median HCV-RNA levels were 5.98 log10 IU/mL in females and 5.73 log10 IU/mL in males; 40 subjects were HIV infected, 29 of those virally suppressed. Markers of HBV infection were identified in 81.8% of males vs. 47.1% of females (p<0.05) and 70% overall, with 6% more being positive only for anti-HBs. The most common pattern was anti-HBc alone (37%) followed by anti-HBc + anti-HBs (33%) and HBsAg + anti-HBc + anti-HBs in one case (male, 54 years, HIV coinfected). HBsAg Next identified four more positive: one female, three males, three HIV-coinfected, two positive for anti-HBc + anti-HBs, two only for anti-HBc. No significant correlation between HCV-RNA levels and HBsAg positivity was found. Conclusions: There's a high rate of HBV coinfection in chronic, unvaccinated HCV carriers. The frequency of overt HBV infection, detected by a highly sensitive HBsAg assays, is relevant and monitoring HBV infection during and after DAA treatment for HCV shall be warranted.